Research on Site Suitability for Solar and Wind Energy in Developing Countries Using Combination of GIS- AHP; A Case Study of Pakistan - Muhammad Ali Raza (00000321060); Dr Muhammad Yousif (USPCAS-E, NUST, Islamabad, 2022)
TH-450
Keywords: MS-EEP Thesis MS Thesis